2018
DOI: 10.1186/s12951-018-0347-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured surface topographies have an effect on bactericidal activity

Abstract: BackgroundDue to the increased emergence of antimicrobial resistance, alternatives to minimize the usage of antibiotics become attractive solutions. Biophysical manipulation of material surface topography to prevent bacterial adhesion is one promising approach. To this end, it is essential to understand the relationship between surface topographical features and bactericidal properties in order to develop antibacterial surfaces.ResultsIn this work a systematic study of topographical effects on bactericidal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
122
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 31 publications
3
122
1
Order By: Relevance
“…Moreover, the heating-induced segmentation synergistically increases the solubility [67] and so antibacterial activity [21,22,67]. Furthermore, it is well known that nanoscale protrusions like the generated Ag 2 O NPs (Figure 1c) can physically kill bacteria by causing cytoplasmic leakage by piercing the bacterial cell wall [68,69]. Hence, in this study, the segmentation (Figure 1) and pre-oxidation (Figure 2a) of the AgNW film by heat-treatment is estimated to enhance the antibacterial activity by facilitating the dissolution and activating the physical contact killing mechanism by nano-level Ag 2 O NPs.…”
mentioning
confidence: 99%
“…Moreover, the heating-induced segmentation synergistically increases the solubility [67] and so antibacterial activity [21,22,67]. Furthermore, it is well known that nanoscale protrusions like the generated Ag 2 O NPs (Figure 1c) can physically kill bacteria by causing cytoplasmic leakage by piercing the bacterial cell wall [68,69]. Hence, in this study, the segmentation (Figure 1) and pre-oxidation (Figure 2a) of the AgNW film by heat-treatment is estimated to enhance the antibacterial activity by facilitating the dissolution and activating the physical contact killing mechanism by nano-level Ag 2 O NPs.…”
mentioning
confidence: 99%
“… Velic et al (2019) studied the effect of varied design parameters of nanopatterns on bacteria behavior by developing a two-dimensional finite element model and demonstrated that reducing the pillar diameter could effectively promote bactericidal efficiency. Additionally, preparing nanopillar structures with similar diameters but different densities and heights showed that extra stretched nanopillars with varying heights leads to rupture in the bacterial cell membranes (the membranes exceeded the threshold value of stretching) ( Wu et al, 2018 ).…”
Section: Bionic Nanostructuresmentioning
confidence: 99%
“…Although a variety of antibacterial surfaces have been developed using different materials, our knowledge of how geometrical variations in these nanopillars can influence the bactericidal activity remains limited. The influence of a nanoscale topology on the bactericidal efficiency has been previously investigated [12,13], but these studies focused on non-uniform surface geometries resulting from nanofabrication techniques that inherently change multiple aspects of nanostructures at once. This is not ideal for the optimization of key geometrical features, like the height, diameter, and spacing of the nanopillars, as their effects cannot be studied independently.…”
Section: Introductionmentioning
confidence: 99%